Identification Of Color, Structure, And Consistency of Soil on Limestone Land in Ratatotok Sub-District - Thaif, Sultan Ariansyah; Soputan, Ronny; Mawara, Jody (Soil and Environment Journal, 2024)
The diversity of soil color, structure, and consistency in limestone land is fascinating to study. This study aims to identify the color, structure, and consistency of the soil on limestone land in North Ratatotok Village, Ratatotok District, Southeast Minahasa Regency. This research was carried out from April to June 2023. The method used in this study was surveys and direct observations in the field. Determining where to observe the soil is done by purposive sampling. Keywords: Soil Color, Soil Structure, Soil Consistency, Limestone Soil Abstrak Keanekaragaman warna tanah, struktur tanah dan konsistensi tanah pada lahan kapur sangat menarik untuk diteliti. Penelitian ini bertujuan untuk mengidentifikasi warna, struktur, dan konsistensi tanah pada lahan kapur di Desa Ratatotok Utara, Kecamatan Ratatotok, Kabupaten Minahasa Tenggara. Penelitian ini dilaksanakan pada bulan April sampai dengan Juni 2023. Metode yang digunakan dalam penelitian ini adalah survei dan pengamatan langsung di lapangan. Penentuan lokasi pengamatan tanah dilakukan dengan cara purposive sampling. Kata Kunci : Warna Tanah, Struktur Tanah, Konsistensi Tanah, Tanah Kapur